2003
DOI: 10.1530/eje.0.1490317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GH replacement therapy in two male siblings with combined X-linked hypophosphatemia and partial GH deficiency

Abstract: Objective: X-linked hypophosphatemia (XLH) is characterized by low serum phosphorus, relative 1,25-dihydroxyvitamin D 3 deficiency and rickets. It is caused by mutations in the phosphate-regulating gene with homologies to endopeptidases on the X chromosome (PHEX). The conventional treatment of XLH includes the administration of phosphate and calcitriol; however, treated patients usually present with a short stature. Therefore, additional coexistent defects, such as GH deficiency, are under debate. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Despite the absence of a gene dose effect, and that of a phenotype-genotype correlation [4,6], most authors observed more severe a disease in affected boys than in girls [3,18,22]. In our series boys were also over-represented among short patients, even in those treated since a very young age; once again, absence of a statistical relationship between male gender and growth failure may be related to the sample size.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Despite the absence of a gene dose effect, and that of a phenotype-genotype correlation [4,6], most authors observed more severe a disease in affected boys than in girls [3,18,22]. In our series boys were also over-represented among short patients, even in those treated since a very young age; once again, absence of a statistical relationship between male gender and growth failure may be related to the sample size.…”
Section: Discussioncontrasting
confidence: 64%
“…Further, rhGH in XLHR has been associated with disproportionate growth in favor of the trunk [17], viewed as a negative outcome [5], although most reports did not demonstrate such disproportionate growth [1,2,10,22,23]. Our experience with rhGH in short children with XLHR ( Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Adults with XLH have a significantly reduced final height up to 20 cm, mean standard deviation score (SDS) of −1.9 [44], but there is a great variability among individuals. XLH patients are not abnormally small at birth [46]; XLH girls and boys seem to have normal growth spurt and adult men show a more severe Fig. 1 Phosphorus metabolism in XLH.…”
Section: Xlh and Growthmentioning
confidence: 99%
“…Addition of growth hormone (GH) to phosphate and 1-hydroxy vitamin D metabolite treatment has been used to improve growth in stunted children with XLH. Although 3-yr GH administration has been shown to accelerate longitudinal growth velocity without worsening body disproportion (9), there is the concern of increasing leg deformities in children responding to GH (9)(10)(11)(12). The effect of GH treatment on mineral and bone metabolism in patients with XLH is to a great extent unknown (13).…”
mentioning
confidence: 99%